Changes of Major Antioxidant Compounds and Radical Scavenging Activity of Palm Oil and Rice Bran Oil during Deep-Frying - Azizah Abdul Hamid; Mohd Sabri Pak Dek; Chin Ping Tan; Mohd Asraf Mohd Zainudin; Evelyn Koh Wee Fang (MDPI AG, 2014)
Changes in antioxidant properties and degradation of bioactives in palm oil (PO) and rice bran oil (RBO) during deep-frying were investigated. The alpha (α)-tocopherol, gamma (γ)-tocotrienol and γ-oryzanol contents of the deep-fried oils were monitored using high performance liquid chromatography, and antioxidant activity was determined using 2-diphenyl-1-picryl hydrazyl (DPPH) radical scavenging activity. Results revealed that the antioxidant activity of PO decreased significantly (p < 0.05), while that of RBO was preserved after deep-frying of fries. As expected, the concentration of α-tocopherol in PO and γ-tocotrienol in both PO and RBO decreased significantly (p < 0.05) with increased frying. Results also showed that γ-tocotrienol was found to be more susceptible to degradation compared to that of α-tocopherol in both PO and RBO. Interestingly, no significant degradation of α-tocopherol was observed in RBO. It is suggested that the presence of γ-oryzanol and γ-tocotrienol in RBO may have a protective effect on α-tocopherol during deep-frying.